Design and fabrication of adjustable table for secondary student - Mohd Azmeer, Alias (2009)
This report presents about the table that always been used especially in lab. This table is an item of furniture comprising an open, flat surface supported by a base or legs that used to hold articles such as food or papers at a convenient or comfortable height when sitting, and is therefore often used in conjunction with chair. In designing such a product or thing for human use, the ‘human factor’ is the important element that must put in consideration. One of the things that regularly used by secondary students when use table. Research had shown that human product that can be adjustable following to the situation, is a product that consider more about the ergonomics terms. The idea of the fabricating of this table is based on student’s creativity. Materials are proposed for the fabrication of the table is a carbon steel material. In this report, we’ll also be having more to the fabrication of this table. The development during the project is to fulfill the learning objective that to produce the adjustable table according to the human factor terms which is secondary students. The variety of applications from the project can be use to produce a product based on human factor.